“In-Vitro Antioxidant Activity of Two Selected Herbal Medicines” - Vinotha, S.; Ira, T.; Sri Ranjani, S. (International Journal of Medical, Health, Pharmaceutical and Biomedical Engineering, 2014)
Hot aqueous and methanol extracts of the two selected herbal medicines such are Vellarugu chooranam (V.C) and Amukkirai Chooranam (A.C) were examined for total phenolic and flavonoid contents and in vitro antioxidant activity using four different methods. The total phenolic and flavonoid contents in methanol extract of V.C were found to be higher (44.41±1.26mg GAE/g; 174.44±9.32mg QE/g) than in the methanol extract of A.C (20.56±0.67mg GAE/g; 7.21±0.85mg QE/g). Hot methanol and aqueous extracts of both medicines showed low antioxidant activity in DPPH, ABTS, and FRAP methods and Iron chelating activity not found at highest possible concentration. V.C contains higher concentrations of total phenolic and flavonoid contents than A.C and can also exert greater antioxidant activity than A.C, although the activities demonstrated were lower than the positive control Trolox. The in vitro antioxidant activity was not related with the total phenolic and flavonoid contents of the methanol and aqueous extracts of both herbal medicines (A.C and V.C).
Keywords: Different extracts; Herbal medicine